Composition for anti-fog film on eyeglass lenses and eyeglass lenses
Patent Information
- Application Number
- KR1020237033024
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-31
- Filing Date
- 2022-03-31
- Publication Date
- 2026-09-11
- Estimated Expiration
- 2042-03-31
Smart Images

Figure 112023106296058-PCT00001 
Figure 112023106296058-PCT00002 
Figure 112023106296058-PCT00003
Abstract
Description
Technology Field
[0001] The present disclosure relates to a composition for an anti-fog film on eyeglass lenses and an eyeglass lens. Background Technology
[0002] Conventionally, various technologies have been considered to prevent "fogging" in automotive articles such as headlamps, meter panels, windows, lenses, and mirrors. Regarding technologies to prevent "fogging," it is common to form an anti-fog layer (hereinafter also referred to as an anti-fog film) by applying a surfactant to the surface; however, in this case, the duration of the effect is very short, and the effect cannot be sustained unless the surfactant is reapplied every few days. Furthermore, if contaminants on the optical article are wiped off with water or the like, the anti-fog layer of the surfactant disappears along with the contaminants, and the anti-fog effect is lost. Additionally, the anti-fog layer formed by applying a surfactant to the surface is insufficient to prevent "fogging" in high-humidity environments, leaving room for improvement. Therefore, recently, technologies are being considered to prevent "fogging" by forming an anti-fog film with absorption performance by coating an absorbent material onto the article substrate instead of a surfactant.
[0003] For example, Patent Document 1 describes an anti-fog optical article in which an absorbent film is formed on an optical article substrate, wherein the absorbent film is composed of two or more layers. For example, Patent Document 2 describes an anti-fog optical article in which an absorbent layer is formed on the surface of a glass or plastic substrate, the absorbent layer being mainly composed of a urethane or acrylic resin having specific polyoxyethylene chains, and a water-repellent layer being mainly composed of at least one of an amino-modified silicone or a mercapto-modified silicone is formed on the surface of the absorbent layer. Prior art literature
[0004] Japanese Patent Publication No. 2000-75104, International Publication No. 2013 / 005710 The problem to be solved
[0005] The anti-fog film having absorption performance described in Patent Document 1 or Patent Document 2 has excellent anti-fog properties and anti-fog durability compared to the case where an anti-fog layer is formed by applying a surfactant to the surface in the conventional manner.
[0006] However, since such anti-fog films are typically formed by applying a liquid anti-fog film-forming coating solution onto a substrate to form a film, bubbles already contained in the coating solution or bubbles swept in during application may adhere to the substrate. Consequently, if the anti-fog film dries and hardens while bubbles remain attached to the substrate, the film is formed with the bubble shapes still intact, which degrades the appearance of the resulting product. In particular, for eyeglass lenses, it is necessary to manufacture lenses suitable for each individual's eyes, resulting in a wide variety of shapes; depending on the shape, a large number of bubbles may adhere to the substrate. To address this problem, there has been a demand for an anti-fog solution that suppresses the generation of bubbles.
[0007] Regarding the problem described above, one embodiment of the present disclosure aims to provide a composition for an anti-fog film on an eyeglass lens capable of manufacturing an eyeglass lens with excellent anti-fog properties and appearance, and an eyeglass lens with excellent anti-fog properties and appearance. means of solving the problem
[0008] The embodiments of the present disclosure relate to the following [1] to [8].
[0009] [1] A composition for an anti-fogging film for eyeglass lenses, having a viscosity of 20 mPa·s or more and 80 mPa·s or less at 15 ℃ and a solid content of 10 mass% or more and 25 mass% or less.
[0010] [2] A composition for an anti-fogging film for eyeglass lenses as described in [1], having a viscosity of 24 mPa·s or higher.
[0011] [3] A composition for an anti-fogging film for eyeglass lenses as described in [1] or [2], wherein the above solid content is 17 mass% or more.
[0012] [4] A composition for an anti-fogging film for eyeglass lenses as described in any one of [1] to [3], comprising components (A) to (C).
[0013] Component (A): A (meth)acrylic resin having a constituent unit derived from a monomer (a-1) represented by the following general formula (1), a constituent unit derived from a monomer (a-2) represented by the following general formula (2), a constituent unit derived from a hydroxyalkyl (meth)acrylate (a-3), and a constituent unit derived from a monomer (a-4) represented by the following general formula (3).
[0014] Component (B): Polyol compound (B)
[0015] Components (C): Polyfunctional isocyanate compounds (C)
[0016] [Chemical Formula 1]
[0017]
[0018] [In general formula (1), R1 is a hydrogen atom or a methyl group, and R2 and R3 are each independently a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, and R2 and R3 may be the same or different.]
[0019] [Chemical Formula 2]
[0020]
[0021] [In general formula (2), R4 is a hydrogen atom or a methyl group, and m is an integer from 1 to 5.]
[0022] [Chemical Formula 3]
[0023]
[0024] [In general formula (3), R5 is a hydrogen atom or a methyl group, R6 is a divalent organic group, and n is an integer greater than or equal to 0 or 1.]
[0025] [5] An eyeglass lens having a fogging film formed by curing the composition for an eyeglass lens fogging film described in any one of [1] to [4] above.
[0026] [6] The above anti-fog film, the outermost layer, is the spectacle lens described in [5] above.
[0027] [7] The above spectacle lens has a substrate and has a fogging film directly on the substrate, the spectacle lens described in [5] or [6].
[0028] [8] An eyeglass lens described in any one of [5] to [7], wherein the above anti-fog film is a single layer. Effects of the invention
[0029] According to one embodiment of the present disclosure, a composition for an anti-fog film for an eyeglass lens that can be manufactured to have excellent anti-fog properties and appearance, and an eyeglass lens having excellent anti-fog properties and appearance can be provided. Specific details for implementing the invention
[0030] The embodiments and examples of the present disclosure are described below. Identical or equivalent parts are assigned the same reference numerals, and descriptions thereof may not be repeated. In the embodiments and examples described below, when mentioning numbers, quantities, etc., the scope of the present disclosure is not necessarily limited to such numbers, quantities, etc., unless specifically stated otherwise. In the embodiments below, each component is not necessarily essential to the embodiments and examples of the present disclosure, except where specifically stated otherwise.
[0031] In the notation of a group (atomic group) in this specification, a notation that does not specify whether it is substituted or unsubstituted includes both those that do not have substituents and those that have substituents. For example, "alkyl group" includes an alkyl group that does not have substituents (unsubstituted alkyl group) and an alkyl group that has substituents (substituted alkyl group).
[0032] In this specification, the notation "(meth)acrylic" refers to a concept that includes both acrylic and methacrylic. The same applies to similar notations such as "(meth)acrylate."
[0033] In this specification, a constituent unit derived from monomer (a-1) is referred to as “constituent unit (a-1),” a constituent unit derived from monomer (a-2) is referred to as “constituent unit (a-2),” a constituent unit derived from monomer (a-3) is referred to as “constituent unit (a-3),” and a constituent unit derived from monomer (a-4) is referred to as “constituent unit (a-4).”
[0034] In the present disclosure, the “viscosity” of the composition for an anti-fog film on eyeglass lenses (hereinafter also referred to as the composition for an anti-fog film) is a value measured at a temperature of 15°C in accordance with 11 of JIS Z 8803:2011 (method for measuring viscosity by a vibratory viscometer). Examples of vibratory viscometers include the vibratory viscometer “VM-10A” (manufactured by Seconic Co., Ltd.).
[0035] In a composition for an anti-fogging film, "solid content" refers to the amount of components other than the solvent.
[0036] The term "number of carbons" for a group having a substituent refers to the number of carbons in the portion excluding the substituent.
[0037] [Composition for Anti-fog Films on Eyeglass Lenses]
[0038] The anti-fogging membrane composition related to the embodiment of the present disclosure has a viscosity at 15°C of 20 mPa·s or more and 80 mPa·s or less, and a solid content of 10 mass% or more and 25 mass% or less.
[0039] In this way, by setting the viscosity and solid content of the anti-fog film composition to the above range, bubbles already contained in the anti-fog film composition or bubbles swept in during application can be immediately brought to the surface, and it is believed that the anti-fog film composition is suppressed from forming and curing a film on a substrate for eyeglass lenses while containing bubbles. As a result, it is possible to suppress the formation of an anti-fog film while the shape of the bubbles remains. Furthermore, by setting the viscosity and solid content of the anti-fog film composition to the above range, it is possible to suppress liquid pooling caused by the anti-fog film composition at the periphery of the lens, which would cause the film thickness of the anti-fog film in that area to become thick and result in an appearance defect.
[0040] In addition, by having the above viscosity and the above solid content, the composition for the anti-fog film can secure a film thickness that can become an anti-fog film having excellent anti-fog properties.
[0041] <Viscosity>
[0042] The viscosity of the anti-fog film composition is, at 15°C, preferably 22 mPa·s or more, more preferably 23 mPa·s or more, and even more preferably 24 mPa·s or more, from the perspective of obtaining an eyeglass lens with better anti-fog properties, and preferably 65 mPa·s or less, more preferably 50 mPa·s or less, and even more preferably 45 mPa·s or less, from the perspective of obtaining an eyeglass lens with good appearance.
[0043] <Solid Content>
[0044] The solid content of the anti-fog film composition is preferably 13 mass% or more, more preferably 15 mass% or more, even more preferably 16 mass% or more, and even more preferably 17 mass% or more, from the perspective of obtaining an eyeglass lens with better anti-fog properties, and is preferably 24.8 mass% or less from the perspective of obtaining an eyeglass lens with good appearance.
[0045] A composition for an anti-fogging film preferably comprises the following components (A) to (C) in order to obtain an anti-fogging film with excellent anti-fogging properties.
[0046] Component (A): A (meth)acrylic resin having a constituent unit derived from a monomer (a-1) represented by the following general formula (1), a constituent unit derived from a monomer (a-2) represented by the following general formula (2), a constituent unit derived from a hydroxyalkyl (meth)acrylate (a-3), and a constituent unit derived from a monomer (a-4) represented by the following general formula (3).
[0047] Component (B): Polyol compound (B)
[0048] Components (C): Polyfunctional isocyanate compounds (C)
[0049] [Chemical Formula 4]
[0050]
[0051] [In general formula (1), R1 is a hydrogen atom or a methyl group, and R2 and R3 are each independently a hydrogen atom or a straight-chain or branched alkyl group having 1 to 3 carbon atoms.]
[0052] [Chemical Formula 5]
[0053]
[0054] [In general formula (2), R4 is a hydrogen atom or a methyl group, and m is an integer from 1 to 5.]
[0055] [Chemical Formula 6]
[0056]
[0057] [In general formula (3), R5 is a hydrogen atom or a methyl group, R6 is a divalent organic group, and n is an integer greater than or equal to 0 or 1.]
[0058] The constituent unit (a-1) included in component (A) (also called (meth)acrylic resin) has an amide group, is highly hydrophilic, and is prone to absorbing moisture. For this reason, it is thought that moisture attached to the surface of the anti-fog film obtained by curing the anti-fog film composition is easily absorbed into the cured film. In addition, it is thought that by incorporating the polyol compound (B), it is possible to create gaps that sufficiently absorb moisture while maintaining the crosslinking density required for the anti-fog film. For these reasons, it is thought that anti-fog properties are imparted.
[0059] In addition, the constituent unit (a-2) included in the resin (A) is a constituent unit having a polycaprolactone structure, and its flexible chemical framework contributes to the improvement of the flexibility and elasticity of the anti-fog membrane. Furthermore, by including a constituent unit (a-3) that is more rigid than the constituent unit (a-2), a balance of flexibility and elasticity is secured. On the other hand, the polydimethylsiloxane chain of the constituent unit (a-4) contributes to the improvement of the anti-fog membrane's slipperiness. Therefore, when an external force is applied to the anti-fog membrane, the two effects mentioned above are synergistically expressed, such that the external force is absorbed by the flexibility and elasticity of the anti-fog membrane while the external force is released from the anti-fog membrane by the slipperiness, and as a result, it is thought that the anti-fog membrane becomes less susceptible to scratches.
[0060] A composition for an anti-fogging membrane preferably has, for every 100 mass% of the total constituent units constituting component (A), a ratio of constituent units derived from monomer (a-1) of 20 mass% or more and 65 mass% or less, a ratio of constituent units derived from monomer (a-2) of 10 mass% or more and 40 mass% or less, and a ratio of constituent units derived from monomer (a-4) of 1 mass% or more and 10 mass% or less, and the ratio (NCO) / (OH) of the total amount (OH) obtained by adding the number of isocyanate groups (NCO) contained in component (C), the number of hydroxyl groups contained in component (A), and the number of hydroxyl groups contained in component (B) is 0.15 or more and 0.55 or less.
[0061] It is believed that by configuring the composition of the anti-fog film in this way, the balance (quantity ratio) of the constituent unit (a-2) and constituent unit (a-3) having hydroxyl groups in component (A) is maintained, and the equivalent ratio (NCO / OH) is set to a specific range less than 1, thereby increasing the hardness of the anti-fog film to the extent that frictional resistance is improved. Additionally, it is believed that by maintaining the compositional balance of the constituent unit (a-2) and constituent unit (a-3) having hydroxyl groups in component (A), and also setting the equivalent ratio (NCO / OH) to a specific range less than 1, the crosslinking density of the anti-fog film is increased and the solvent resistance of the anti-fog film is improved.
[0062] The components contained in the anti-fog membrane composition of the present embodiment will be described below.
[0063] <Component (A): (Met)acrylic resin>
[0064] The composition for the anti-fogging film of the present embodiment preferably comprises a (meth)acrylic resin, which is component (A), that is, a constituent unit derived from a monomer (a-1) represented by general formula (1), a constituent unit derived from a monomer (a-2) represented by general formula (2), a constituent unit derived from a hydroxyalkyl (meth)acrylate (a-3), and a constituent unit derived from a monomer (a-4) represented by general formula (3).
[0065] As mentioned above, it is thought that the constituent unit (a-1) is mainly involved in the absorption of water (moisture).
[0066] (Meth)acrylic resins can typically be obtained by polymerizing monomers (a-1), monomer (a-2), monomer (a-3), and monomer (a-4). Details of the polymerization method will be described later.
[0067] In addition, in the present embodiment, 100% of the constituent units constituting the (meth)acrylic resin do not have to be constituent units derived from (meth)acrylic monomers. That is, the (meth)acrylic resin may include some (but not all) constituent units derived from monomers that are not (meth)acrylic.
[0068] In order to fully obtain the effects derived from the (meth)acrylic structure, it is preferable that at least 50 mass% of the total constituent units of the (meth)acrylic resin are constituent units derived from (meth)acrylic monomers. More preferably, at least 80 mass% of the total constituent units of the (meth)acrylic resin are constituent units derived from (meth)acrylic monomers. Even more preferably, all (100%) constituent units of the (meth)acrylic resin are constituent units derived from (meth)acrylic monomers.
[0069] Monomer (a-1) is not particularly limited as long as it has the structure of the general formula (1) described above. Specifically, examples include (meth)acrylamide, N-methylacrylamide, N,N-dimethyl(meth)acrylamide, N-ethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, Nn-propyl(meth)acrylamide, N-isopropyl(meth)acrylamide, etc.
[0070] Monomer (a-1) may be used in combination of at least one type or two or more types. For example, a (meth)acrylic resin may be obtained by carrying out a polymerization reaction using two or more of the monomers exemplified above.
[0071] Monomer (a-1) is particularly preferably composed of N,N-dimethyl(meth)acrylamide and N,N-diethyl(meth)acrylamide, in order to improve the anti-fogging performance of the anti-fogging film and to suppress the occurrence of fogging in the steam test.
[0072] In the present embodiment, it is preferable that the constituent unit derived from monomer (a-1) in the (meth)acrylic resin be included in an amount of 20 to 65 mass% with respect to the total constituent unit of the resin. More preferably, it is 35 to 60 mass%, and even more preferably 40 to 55 mass%. If the constituent unit derived from monomer (a-1) is 20 mass% or more, it is easier to form an anti-fog film that exhibits anti-fog performance suitable for practical use, and if it is 65 mass% or less, the relative decrease in the proportion of constituent units derived from other monomers is avoided, making it easier to maintain the balance as a whole composition.
[0073] Monomer (a-2) is not particularly limited as long as it has the structure of the aforementioned general formula (2).
[0074] In the present embodiment, the (meth)acrylic resin comprises a constituent unit derived from monomer (a-2) in an amount of preferably 10 to 40 mass%, more preferably 20 to 38 mass%, and even more preferably 25 to 35 mass% with respect to the total constituent unit of the resin.
[0075] If the constituent unit derived from monomer (a-2) is 10 mass% or more, the flexibility of the anti-fog membrane is easily secured, and if it is 40 mass% or less, the elasticity of the anti-fog membrane is easily secured.
[0076] (Met)acrylic resins may contain multiple types of repeating units derived from monomer (a-2).
[0077] Monomer (a-3) is a hydroxyalkyl (meth)acrylate. Specific examples include, for instance, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, etc. In the present embodiment, among these, hydroxyethyl (meth)acrylate is preferred.
[0078] In this embodiment, the constituent unit derived from monomer (a-3) in the (meth)acrylic resin is preferably 1 to 30 mass%, more preferably 2 to 20 mass%, and even more preferably 3 to 15 mass% with respect to the total constituent unit of the (meth)acrylic resin.
[0079] In addition, monomer (a-3) has a hydroxyl group similar to monomer (a-2) and undergoes a cross-linking reaction with the polyfunctional isocyanate compound described later to form an anti-fog film.
[0080] In this embodiment, the anti-fog film is formed not by generating a cross-linking reaction with only the monomer (a-2), but by generating a cross-linking reaction with the polyfunctional isocyanate compound together with the monomer (a-3), an anti-fog film with various physical properties can be formed.
[0081] As described above, the (meth)acrylic resin is a resin that has hydroxyl groups overall, that is, has hydroxyl groups, because it contains constituent units derived from monomer (a-2) and monomer (a-3). For this reason, it can form a cross-linked structure by reacting with the polyfunctional isocyanate compound described below together with the polyol compound described below.
[0082] The hydroxyl group value of the (meth)acrylic resin is preferably 40 to 150 mgKOH / g, more preferably 70 to 140 mgKOH / g, and even more preferably 90 to 130 mgKOH / g.
[0083] By setting the value within this range, the cross-linking structure can be properly controlled by reacting with the polyfunctional isocyanate compound (described later) together with the polyol compound (described later). As a result, it becomes possible to harden the anti-fog film while maintaining the flexibility and elasticity of the anti-fog film. Therefore, it becomes easier to achieve a higher level of compatibility with the anti-fog film's scratch resistance, reduced friction resistance, and solvent resistance.
[0084] In addition, hydroxyl group refers to the number of milligrams of potassium hydroxide required to neutralize the acetic acid combined with the hydroxyl group when 1 g of the sample is acetylated.
[0085] Monomer (a-4) is not particularly limited as long as it has the structure of the aforementioned general formula (3).
[0086] The (meth)acrylic resin may contain multiple types of repeating units derived from monomer (a-4). For example, the (meth)acrylic resin may be obtained by carrying out a polymerization reaction using two or more of the monomers exemplified above.
[0087] In this embodiment, the constituent unit derived from monomer (a-4) in the (meth)acrylic resin is preferably 1 to 10 mass%, more preferably 2 to 8 mass%, and even more preferably 3 to 7 mass% with respect to the total constituent unit of the resin.
[0088] If the constituent unit derived from monomer (a-4) is 1 mass% or more, it becomes easier to obtain an anti-fog film that satisfies scratch resistance. If it is 10 mass% or less, it becomes easier to synthesize a homogeneous (meth)acrylic resin.
[0089] The (meth)acrylic resin may include, or may not include, any constituent unit (constituent unit (a-5)) other than constituent unit (a-1), constituent unit (a-2), constituent unit (a-3), and constituent unit (a-4). For example, constituent unit (a-5) may be a constituent unit derived from the monomers shown below. By including such constituent units in the (meth)acrylic resin, the glass transition temperature of the (meth)acrylic resin and the physical properties of the anti-fog film (hardness, flexibility, etc. of the anti-fog film) can be adjusted and optimized.
[0090] As for the constituent unit (a-5), examples include a constituent unit derived from a monomer in the general formula CH2=CR-COO-R', where R is a hydrogen atom or a methyl group and R' is an alkyl group, a monocyclic or polycyclic cycloalkyl group, an aryl group, or an aralkyl group.
[0091] Specific examples of this monomer include, for instance, methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isodecyl (meth)acrylate, n-lauryl (meth)acrylate, n-stearyl (meth)acrylate, phenyl (meth)acrylate, benzyl (meth)acrylate, etc.
[0092] Among these, it is preferable that R' is an alkyl group having 1 to 8 carbon atoms, more preferable that R' is an alkyl group having 1 to 6 carbon atoms, and even more preferable that R' is an alkyl group having 1 to 4 carbon atoms.
[0093] The (meth)acrylic resin may include multiple types of repeating units corresponding to the constituent unit (a-5). For example, the (meth)acrylic resin may be obtained by carrying out a polymerization reaction using two or more of the monomers exemplified as specific examples above.
[0094] When the (meth)acrylic resin contains a constituent unit (a-5), the content thereof is preferably 1 to 40 mass%, more preferably 3 to 30 mass%, and even more preferably 5 to 20 mass% with respect to the total constituent unit of the (meth)acrylic resin.
[0095] The mass average molecular weight (Mw) of the (meth)acrylic resin is not particularly limited, but is preferably 10,000 to 100,000, more preferably 20,000 to 70,000, and even more preferably 30,000 to 60,000. If the mass average molecular weight is 10,000 or more, the desired anti-fogging performance is easily obtained, and if it is 100,000 or less, the paintability when applied to a workpiece such as eyeglass lenses tends to be excellent.
[0096] In addition, the mass average molecular weight can be obtained by gel permeation chromatography (GPC) using polystyrene as a standard material.
[0097] The glass transition temperature of the (meth)acrylic resin is not particularly limited, but is preferably 20 to 120 ℃, more preferably 30 to 110 ℃, and even more preferably 35 to 100 ℃.
[0098] In addition, the glass transition temperature of (meth)acrylic resins can be determined by various methods, but for example, it can be determined based on Fox's formula below.
[0099] 1 / Tg = (W1 / Tg1) + (W2 / Tg2) + (W3 / Tg3) + … + (W n / Tg n )
[0100] [In the formula, Tg is the glass transition temperature (K) of the (meth)acrylic resin, W1, W2, W3… W n silver, mass fraction of each monomer, Tg1, Tg2, Tg3… Tg n represents the glass transition temperature (K) of a homopolymer composed of monomers corresponding to the mass fraction of each monomer, respectively.
[0101] In this specification, the glass transition temperature of the (meth)acrylic resin (not the glass transition temperature of the anti-fog film, but the glass transition temperature of the (meth)acrylic resin alone) refers to the glass transition temperature obtained based on the above formula. In addition, for monomers whose glass transition temperature is unclear, such as special monomers, polyfunctional monomers, etc., the glass transition temperature is obtained using only monomers whose glass transition temperature has been determined.
[0102] (Meth)acrylic resins can typically be obtained by polymerization. Various methods such as radical polymerization, cationic polymerization, and anionic polymerization may be used for the polymerization reaction, among which radical polymerization is preferred. Furthermore, the polymerization may be any of solution polymerization, suspension polymerization, and emulsion polymerization. Among these, solution polymerization is preferred from the perspective of precise control of the polymerization process.
[0103] Known initiators may be used as polymerization initiators for radical polymerization. Examples include azo-based initiators such as azobis(isobutyronitrile), 2,2-azobis(2-methylbutyronitrile), 2,2-azobis(2-methylpropionitrile), and 2,2-azobis(2,4-dimethylvaleronitrile); peroxide-based initiators such as benzoyl peroxide, t-butylperoxyoctanoate, diisobutyl peroxide, di(2-ethylhexyl)peroxypivalate, decanoyl peroxide, t-butylperoxy-2-ethylhexanoate, and t-butylperoxybenzoate; and redox-based initiators combining an oxidizing agent and a reducing agent, such as hydrogen peroxide and iron (II) salt, persulfate and sodium bisulfite. These may be used as a single type or in combination of two or more types.
[0104] The amount of polymerization initiator is not particularly limited, but it is preferable to have 0.001 to 10 parts by mass when the total amount of the monomer mixture to be polymerized is 100 parts by mass.
[0105] In addition, appropriately known chain transfer agents, polymerization inhibitors, molecular weight adjusters, etc. may be used during the polymerization reaction. Furthermore, the polymerization reaction may be carried out in one step or in two or more steps. The temperature of the polymerization reaction is not particularly limited, but is typically within the range of 50°C to 200°C, preferably 80°C to 150°C.
[0106] <Component (B): Polyol Compound>
[0107] The composition for the anti-fog film of the present embodiment preferably includes a polyol compound. By including a polyol compound, it becomes possible to form an anti-fog film with superior anti-fog durability by reacting with the polyfunctional isocyanate compound described later together with the (meth)acrylic resin. The number of hydroxyl groups in one molecule of the polyol compound is 2 or more, preferably 2 to 6, and more preferably 2 to 4.
[0108] The polyol compound preferably comprises at least one polyol compound selected from the group consisting of polycaprolactone polyol, polycarbonate polyol, and polyether polyol. The chemical structure of these compounds is moderately flexible and also elastic. Because of this, the flexibility and elasticity of the cured film can be further increased.
[0109] Polycaprolactone polyols can be used without particular restriction as long as they are compounds having a ring-opening structure of caprolactone and two or more hydroxyl groups in one molecule.
[0110] Polycarbonate polyols can be used without particular restriction as long as they are compounds having a carbonate group represented as -O-(C=O)-O- and two or more hydroxyl groups in one molecule. Polycarbonate polyols can be obtained by reacting one or more polyol raw materials (polyhydric alcohols) with a carbonate ester or phosgene.
[0111] As for the polyol raw material, there are no particular limitations, but examples include aliphatic polyols, polyols having a cycloaliphatic structure, aromatic polyols, etc. In this embodiment, an aliphatic polyol not having a cycloaliphatic structure is preferred from the perspective of the flexibility of the cured film.
[0112] Examples of carbonate esters include aliphatic carbonate esters such as dimethyl carbonate and diethyl carbonate, aromatic carbonate esters such as diphenyl carbonate, and cyclic carbonate esters such as ethylene carbonate. Among these, aliphatic carbonate esters are preferred due to ease of availability and manufacturing, and dimethyl carbonate is particularly preferred.
[0113] Polyether polyols can be used without particular restriction if they are compounds having an ether bond (-O-) and two or more hydroxyl groups in one molecule.
[0114] Specific compounds include, for example, low molecular weight polyols such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, 3-methyl-1,5-pentanediol, 3,3-dimethylolheptane, diethylene glycol, dipropylene glycol, neopentyl glycol, cyclohexane-1,4-diol, cyclohexane-1,4-dimethanol, dimersandiols, bisphenol A, bis(β-hydroxyethyl)benzene, xylylene glycol, glycerin, trimethylolpropane, pentaerythritol, etc., or ethylenediamine, propylenediamine, toluenediamine, metaphenylenediamine, Examples include polyether polyols obtained by addition polymerization of alkylene oxides such as ethylene oxide, propylene oxide, butylene oxide, etc., using a compound having two or more, preferably two to three, active hydrogen groups such as low molecular weight polyamines such as diphenylmethanediamine and xylylenediamine as an initiator, or polyether polyols obtained by ring-opening polymerization of alkylglycidyl ethers such as methylglycidyl ether, arylglycidyl ethers such as phenylglycidyl ether, and cyclic ether monomers such as tetrahydrofuran.
[0115] In addition, in the present embodiment, the polyol compound may be a compound corresponding to a plurality of polycaprolactone polyols, polycarbonate polyols, and polyether polyols. For example, the polyol compound may be a polyether-polyester polyol having ether bonds and ester bonds.
[0116] In addition, the polyol compound may include multiple types among polycaprolactone polyol, polycarbonate polyol, and polyether polyol.
[0117] The hydroxyl group value of the polyol compound is preferably 50 to 500 mgKOH / g, more preferably 100 to 350 mgKOH / g, and even more preferably 150 to 250 mgKOH / g. By using an appropriate amount of hydroxyl groups, the cross-linking structure resulting from the reaction with the following polyfunctional isocyanate compound is controlled, making it easier to further increase the flexibility and elasticity of the cured film.
[0118] In this embodiment, the mass average molecular weight (Mw) of the polyol compound is preferably 450 to 2,500, more preferably 500 to 1,500, and even more preferably 500 to 700. By using an appropriate molecular weight, it becomes easier to achieve a higher degree of compatibility between suppressing changes in the appearance of the cured film due to improved flexibility and elasticity, and the durability of the cured film, such as gasoline resistance.
[0119] The content of the polyol compound in the coating composition is, with respect to 100 parts by mass of (meth)acrylic resin, preferably 5 to 200 parts by mass, more preferably 15 to 180 parts by mass, even more preferably 20 to 150 parts by mass, even more preferably 20 to 100 parts by mass, even more preferably 20 to 50 parts by mass, and even more preferably 20 to 40 parts by mass. By using this numerical range, it becomes easier to obtain performance derived from the polyol compound and easier to balance with other components.
[0120] In the present embodiment, among the aforementioned polycaprolactone polyol, polycarbonate polyol, and polyether polyol, it is preferable to include polycaprolactone polyol, and among the polycaprolactone polyol, it is particularly preferable to include polycaprolactone diol (a compound having a caprolactone structure and also having two hydroxyl groups).
[0121] This is because the (meth)acrylic resin, which is component (A), has the structure of the general formula (2) described above, that is, the caprolactone structure, so the polyol compound tends to have good compatibility with the resin and tends to improve anti-fogging performance without excessively increasing the crosslinking density.
[0122] <Component (C): Polyfunctional isocyanate compound>
[0123] The composition for the anti-fog film of the present embodiment preferably includes a polyfunctional isocyanate compound as component (C). By including the polyfunctional isocyanate compound in the composition for the anti-fog film, the hydroxyl groups of the constituent unit (a-2) and constituent unit (a-3) included in the (meth)acrylic resin of component (A), and the hydroxyl groups of the polyol compound of component (B) undergo a cross-linking reaction with the polyfunctional isocyanate compound, thereby forming an anti-fog film with excellent anti-fog durability.
[0124] A polyfunctional isocyanate compound is a compound having two or more isocyanate groups (including isocyanate groups protected by sulcitric groups) in one molecule. Preferably, the number of functional groups in the polyfunctional isocyanate compound is more preferably 2 to 6 per molecule, and even more preferably 2 to 4 per molecule.
[0125] Examples of polyfunctional isocyanate compounds include aliphatic diisocyanates such as lysine isocyanate, hexamethylene diisocyanate, and trimethylhexane diisocyanate; hydrogenated xylylene diisocyanate, isophorone diisocyanate, methylcyclohexane-2,4-(or 2,6)-diisocyanate; cyclic aliphatic diisocyanates such as 4,4'-methylenebis(cyclohexyl isocyanate) and 1,3-(isocyanatomethyl)cyclohexane; and isocyanates with three or more functions such as lysine triisocyanate.
[0126] In addition to the above, the polyfunctional isocyanate compound of component (C) may be used as a polymer of the same, such as a biuret type, isocyanurate type, or adduct type. Among these, a biuret-type polyfunctional isocyanate compound having appropriate rigidity is preferred.
[0127] In the present embodiment, the content of the polyfunctional isocyanate compound in the coating composition is not particularly limited as long as it is formulated according to the equivalent ratio (NCO) / (OH) described below, but is typically 5 to 100 parts by mass, preferably 7 to 75 parts by mass, more preferably 10 to 60 parts by mass, even more preferably 10 to 50 parts by mass, even more preferably 15 to 40 parts by mass, and even more preferably 20 to 30 parts by mass per 100 parts by mass of (meth)acrylic resin. By keeping it within this numerical range, it is believed that necessary and sufficient crosslinking is achieved within the cured film.
[0128] The molar amount of isocyanate groups (including block isocyanate groups) contained in the polyfunctional isocyanate compound relative to the hydroxyl groups of the (meth)acrylic resin and polyol compound (i.e., equivalent ratio (NCO) / (OH)) is preferably in the range of 0.15 to 0.55. When the equivalent ratio (NCO) / (OH) is within this range, the crosslinking density is sufficiently high, and as a result, functions such as antifogging and solvent resistance as a cured film are sufficient.
[0129] From this perspective, the equivalent ratio (NCO) / (OH) is preferably 0.25 to 0.50, more preferably 0.35 to 0.45.
[0130] <Forms of compositions for anti-fog membranes>
[0131] The anti-fogging membrane composition of the present embodiment may be of a one-component type, that is, in which all components other than the solvent are substantially uniformly mixed (dissolved or dispersed) in the solvent. When the polyfunctional isocyanate compound is a block isocyanate, a one-component type is preferred.
[0132] In addition, as another aspect, the anti-fog membrane composition of the present embodiment may be of a two-component type. By making it of a two-component type, the preservation of the anti-fog membrane composition can be improved.
[0133] For example, the anti-fogging film composition of the present embodiment may be composed of (1) liquid A, which contains a (meth)acrylic resin and / or a polyol compound and does not contain a polyfunctional isocyanate compound, and (2) liquid B, which contains a polyfunctional isocyanate compound and does not contain a (meth)acrylic resin and a polyol compound, wherein liquid A and liquid B are stored in their respective containers and liquid A and liquid B are mixed immediately before use (coating).
[0134] In this case, components other than (meth)acrylic resins, polyol compounds, and polyfunctional isocyanate compounds (additives, etc.) may be included in liquid A, may be included in liquid B, or may be prepared in other containers.
[0135] In particular, when the polyfunctional isocyanate compound is not a block isocyanate (i.e., when the isocyanate group in the system exists in the form of -NCO), it is preferable that the anti-fogging membrane composition be a two-component type.
[0136] <Dragon Emperor>
[0137] The anti-fog membrane composition of the present embodiment may include a solvent. By using a solvent, it becomes easier to adjust the viscosity and solid content of the anti-fog membrane composition.
[0138] Examples of solvents include aromatic hydrocarbon solvents such as toluene and xylene, alcohol solvents such as methanol, ethanol, isopropyl alcohol, n-butanol, t-butanol, isobutanol, and diacetone alcohol, ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone, ester solvents such as ethyl acetate, propyl acetate, butyl acetate, and isobutyl acetate, and glycol ether solvents such as propylene glycol monomethyl acetate, propylene glycol monomethyl ether, and propylene glycol monomethyl ether acetate.
[0139] Among these, t-butanol, diacetone alcohol, methyl ethyl ketone, ethyl acetate, and propylene glycol monomethyl ether acetate are preferred due to their low reactivity with isocyanates and their solubility and drying properties.
[0140] The solvent content in the composition for the anti-fog film is preferably 20 to 90 mass%, more preferably 30 to 85 mass%, and even more preferably 35 to 80 mass%, from the perspective of controlling the thickness of the anti-fog film.
[0141] The total content of components (A), (B) and (C) in the solid content of the coating composition is preferably 60 mass% or more, more preferably 80 mass% or more, even more preferably 90 mass% or more, and even more preferably 95 mass% or more, and preferably 100 mass% or less, for example, 100 mass%, in order to improve anti-fog and scratch resistance.
[0142] <Other Additives>
[0143] The composition for the anti-fogging film may, if necessary, include additives such as a curing catalyst, a UV absorber, a light stabilizer, a surfactant, a leveling agent, and an antifoaming agent.
[0144] The content of the additive is preferably 0.001 to 5 mass%, more preferably 0.01 to 4 mass%, and even more preferably 0.1 to 3 mass% with respect to the total mass of the coating composition.
[0145] A composition for an anti-fogging film can be prepared by dissolving or dispersing each of the above components used as needed in a solvent.
[0146] Each component may be dissolved or dispersed in a solvent simultaneously or sequentially in any order. There are no particular restrictions on the specific method of dissolution or dispersion, and known methods may be employed without limitation.
[0147] [Eyeglass Lenses]
[0148] An eyeglass lens related to an embodiment of the present disclosure has a substrate and a fogging film formed on the substrate.
[0149] <Lens Material>
[0150] The lens material is, for example, an eyeglass lens material.
[0151] Examples of resins forming the lens substrate include polycarbonate resin, urethaneurea resin, acrylallyl resin, (thio)urethane resin, polysulfide resin, polyamide resin, polyester resin, etc. (thio)urethane resin refers to at least one type selected from thiourethane resin and urethane resin. Among these, (thio)urethane resin and polysulfide resin are preferred.
[0152] In addition, the lens material used in the eyeglass lens of the present embodiment is preferably a refractive index of 1.50 or higher, and more preferably a plastic lens material with a refractive index of 1.60 or higher.
[0153] Examples of commercially available plastic lens materials that are desirable include the allyl carbonate-based plastic lens "HILUX 1.50" (manufactured by HOYA Co., Ltd., refractive index 1.50), the thiourethane-based plastic lens "EYAS" (manufactured by HOYA Co., Ltd., refractive index 1.60), the thiourethane-based plastic lens "MERIA" (manufactured by HOYA Co., Ltd., refractive index 1.60), the thiourethane-based plastic lens "EYNOA" (manufactured by HOYA Co., Ltd., refractive index 1.67), the polysulfide-based plastic lens "EYRY" (manufactured by HOYA Co., Ltd., refractive index 1.70), and the polysulfide-based plastic lens "EYVIA" (manufactured by HOYA Co., Ltd., refractive index 1.74).
[0154] The thickness and diameter of the substrate are not particularly limited, but the thickness is typically about 1 to 30 mm, and the diameter is typically about 50 to 100 mm.
[0155] As for the lens material, it may be either a finished lens or a semi-finished lens.
[0156] The surface shape of the lens material is not particularly limited and may be any of a flat surface, a convex surface, a concave surface, etc.
[0157] The spectacle lenses of the present disclosure may be any of single-focus lenses, multifocal lenses, progressive power lenses, etc. For progressive power lenses, typically, a near-vision area (near vision area) and a progressive area (intermediate area) are included in the aforementioned lower area, and a distance vision area (distance vision area) is included in the upper area.
[0158] <Balmatitis>
[0159] By curing the anti-fog film composition of the present embodiment, an anti-fog film suitable for eyeglass lenses can be formed. By using the anti-fog film composition of the present embodiment, the inclusion of air bubbles in the anti-fog film is suppressed, thereby enabling the manufacture of eyeglass lenses with excellent anti-fog properties and appearance.
[0160] The above anti-fog film is preferably formed as the outermost layer of the eyeglass lens from the perspective of sufficiently exhibiting anti-fog properties. In addition, the above anti-fog film may be formed on only one side or on both sides.
[0161] From the perspective of obtaining an eyeglass lens with excellent anti-fogging properties, it is preferable that the above anti-fogging film be an absorbent layer.
[0162] Here, the statement that the anti-fog film "has absorbency" means that the material constituting the anti-fog film exhibits the characteristic of accepting moisture, and also means that after storing a transparent substrate with an anti-fog film formed thereon at room temperature, when the transparent substrate with the anti-fog film formed thereon is placed at a distance of 35 mm from the surface of hot water at 40°C and exposed to steam from the hot water for 15 seconds, there is no diffuse reflection on the surface of the anti-fog film due to fine water droplets, and there is no deformation due to condensation in the image viewed through the transparent substrate with the anti-fog film formed thereon after contact with steam.
[0163] In addition, it is preferable that the anti-fog film is obtained by curing an anti-fog film composition containing the above components (A) to (C). If it is obtained by curing an anti-fog film composition containing the above components (A) to (C), high durability can be exhibited even if the anti-fog film is located on the outermost layer of the eyeglass lens.
[0164] As one aspect related to the present embodiment, from the perspective of anti-fog durability, it is preferable that the anti-fog film be formed directly on the substrate.
[0165] The anti-fog membrane may be a single layer or a multi-layered anti-fog membrane. From the perspective of productivity, it is preferable for the anti-fog membrane to be a single layer.
[0166] The thickness of the above anti-fog film is preferably 1 to 50 μm, more preferably 3 to 40 μm, even more preferably 5 to 30 μm, and even more preferably 8 to 25 μm, from the perspective of improving anti-fog performance.
[0167] <Other Floors>
[0168] In the eyeglass lens, a functional layer other than an anti-fog film may be formed.
[0169] Examples of the above functional layers include a hard coat layer, an anti-reflective layer, and a primer layer.
[0170] The functional layer may be formed on a first main surface of the lens substrate, may be formed on a second main surface of the lens substrate, or may be formed on both the first and second main surfaces of the lens substrate. Additionally, after forming the functional layer on the lens substrate, an anti-fog film may be formed on the functional layer, or after forming the anti-fog film on the lens substrate, the functional layer may be formed.
[0171] <Method of manufacturing eyeglass lenses>
[0172] In one aspect of the method for manufacturing an eyeglass lens related to the present embodiment, an anti-fog film composition (in the case of a two-component type, a mixture of two components) prepared by dissolving or dispersing each of the above components used as needed in a solvent is coated onto a lens substrate, and an anti-fog film is formed by drying and curing the coating film at a predetermined temperature to obtain an eyeglass lens.
[0173] The coating method is not particularly limited and includes, for example, the air spray method, airless spray method, electrostatic coating method, roll coater method, flow coater method, spin coater method, and dipping method. From the perspective of productivity, the dipping method is preferable.
[0174] After coating, the anti-fog film is obtained by drying and curing at 20 to 160°C for 10 to 120 minutes, preferably at 60 to 120°C for 20 to 90 minutes, and then cooling at room temperature. In addition, the temperature and time for drying and curing can be appropriately adjusted by taking into account the type of solvent or the heat resistance of the lens substrate.
[0175] In addition, if necessary, after forming the functional layer (hard coat layer, primer layer, anti-reflective layer, etc.) described above on the lens substrate, a fogging film may be formed on the functional layer, or after forming the fogging film on the lens substrate, a functional layer may be formed on the fogging film.
[0176] In this disclosure, regarding the examples, contents, and various physical properties of each of the above components, matters described as examples or preferred ranges in the detailed description of the invention may be combined at will.
[0177] In addition, if the composition described in the example is adjusted to become the composition described in the detailed description of the invention, the invention can be practiced in the same way as the example across the entire claimed composition range.
[0178] Examples
[0179] Next, the present disclosure will be explained in more detail by way of examples, but the present disclosure is not limited in any way by these examples.
[0180] The present disclosure will be explained in detail below by way of examples.
[0181] <Measurement and Evaluation>
[0182] Measurement evaluations of the following items were performed on the anti-fog film compositions and spectacle lenses obtained in Examples 1 and 2 and Comparative Examples 1 to 3 below. The results of these measurement evaluations are shown in Table 1.
[0183] (Hydroxyl group)
[0184] It was measured and calculated in accordance with the method specified in “7.1 Neutralization Titration Method” of JIS K 0070 “Test Method for Acid Value, Saponification Value, Ester Value, Iodine Value, Hydroxyl Value and Unsaponifiable Products of Chemical Products”.
[0185] In addition, the acid value used for calculating the hydroxyl value was measured and calculated in accordance with the method specified in "3.1 Neutralization Titration Method" of the above JIS standard.
[0186] (Number average molecular weight (Mn), Mass average molecular weight (Mw), Polydispersity (Mw / Mn))
[0187] It was measured and calculated by gel permeation chromatography (GPC). The apparatus and conditions used are as follows.
[0188] · Equipment Used: HLC8220GPC (Manufactured by Tosoh Co., Ltd.)
[0189] Columns used: TSKgel SuperHZM-M, TSKgel GMHXL-H, TSKgel G2500HXL, TSKgel G5000HXL (Manufactured by Tosoh Co., Ltd.)
[0190] · Column temperature: 40 ℃
[0191] Standard Material: TSKgel Standard Polystyrene A1000, A2500, A5000, F1, F2, F4, F10 (Manufactured by Tosoh Co., Ltd.)
[0192] · Detector: RI (Radiographic Refraction) Detector
[0193] · Eluent: Tetrahydrofuran
[0194] · Flow rate: 1 ml / min
[0195] (Viscosity measurement)
[0196] Measurements were taken at a measurement temperature of 15°C using a vibratory viscometer “VM-10A” (manufactured by Seconic Co., Ltd.). In addition, the measurement method was based on JIS Z 8803:2011 11 (Method for measuring viscosity by vibratory viscometer).
[0197] (Measurement of anti-fog membrane thickness)
[0198] The thickness of the anti-fog film on the obtained eyeglass lens was measured using the non-contact film thickness measuring system “FF8” (manufactured by System Road Co., Ltd.).
[0199] (Anti-fog assessment)
[0200] Under conditions of room temperature of 25°C and humidity of 40%, exhaled air was sprayed onto the surface of the anti-fog film of the obtained spectacle lens for 10 seconds. Visual observation was performed on the condition of the anti-fog film from the start of exhaling until the end of spraying, and an evaluation was performed according to the following evaluation criteria.
[0201] A: No fogging is observed at all (excellent anti-fogging properties)
[0202] B: The blur disappears within 1 second.
[0203] C: Blurring is observed, and it takes more than 10 seconds for the blurring to clear (anti-fog properties are poor)
[0204] (Appearance evaluation)
[0205] The appearance of the obtained eyeglass lenses was evaluated according to the following evaluation criteria.
[0206] A: The anti-fog film does not contain air bubbles, and no liquid accumulation at the periphery of the eyeglass lens is confirmed to be caused by the anti-fog film composition.
[0207] B: Although the anti-fog film does not contain air bubbles, a slight accumulation of liquid originating from the anti-fog film composition can be observed around the periphery of the eyeglass lens.
[0208] C: Although the anti-fog film does not contain air bubbles, it can be confirmed that liquid originating from the anti-fog film composition is present around the periphery of the eyeglass lens.
[0209] D: The anti-fog membrane contains air bubbles.
[0210] [Example 1]
[0211] (Synthesis of (Matte)Acrylic Resins)
[0212] 150 parts by mass of propylene glycol monomethyl acetate (PGMAC) were injected into a 500 ml flask equipped with a stirrer, thermometer, condenser, and nitrogen gas inlet tube, and the temperature was raised to 110°C.
[0213] Separately, 25 parts by mass of dimethylacrylamide (DMAA), 35 parts by mass of polycaprolactone-modified hydroxyethyl acrylate (manufactured by Daicel Co., Ltd., Flaxel FA2D), 10 parts by mass of 2-hydroxyethyl methacrylate (HEMA), 5 parts by mass of single-terminal methacrylate-modified polydimethylsiloxane (manufactured by JNC Co., Ltd., Silaplane FM-0721, molecular weight 5000), 25 parts by mass of methyl methacrylate, and 1 part by mass of 1,1'-azobis(cyclohexane-1-carbonitrile) (manufactured by Wako Pure Chemical Industry Co., Ltd., V-40) were mixed. This mixed monomer was added dropwise to the above 500 ml flask while stirring over a period of 2 hours, and reacted for 5 hours.
[0214] Heating was stopped and cooled to room temperature to obtain a resin solution containing (meth)acrylic resin (solid content ratio: about 40 mass%).
[0215] The hydroxyl value of the obtained (meth)acrylic resin was 57 mgKOH / g, the number average molecular weight (Mn) was 12,000, the mass average molecular weight (Mw) was 44,000, and the polydispersity (Mw / Mn) was 3.67. In addition, based on the aforementioned Fox formula, the glass transition temperature (Tg) of the (meth)acrylic resin calculated from the mixing ratio of the monomers used was 32.8 °C.
[0216] (Preparation of a composition for anti-fog membranes)
[0217] A mixture was obtained by mixing the (meth)acrylic resin obtained above, polycaprolactone diol (manufactured by Daicel Co., Ltd., Fluxel 205U, molecular weight 530, hydroxyl group 207 to 217 mgKOH / g), a polyfunctional isocyanate compound (manufactured by Asahi Kasei Co., Ltd., 24A-100, biuret type of hexamethylene diisocyanate, isocyanate group content 23.5 mass%, solid content 100 mass%), propylene glycol monomethyl ether acetate, diacetone alcohol, methyl ethyl ketone, t-butanol, and ethyl acetate. In addition, the content of each of the obtained mixture is as follows.
[0218] (Met)acrylic resin: 14.7 mass%
[0219] Polycaprolactone diol: 4.4 mass%
[0220] Polyfunctional isocyanate compound: 3.4 mass%
[0221] Propylene glycol monomethyl ether acetate: 28.5 mass%
[0222] Diacetone alcohol: 18.5 mass%
[0223] Methyl ethyl ketone: 13.5 mass%
[0224] t-butanol: 8.5 mass%
[0225] Ethyl acetate: 8.5 mass%
[0226] Then, ethyl acetate, methyl ethyl ketone, and diacetone alcohol were added to and mixed in a mixture to prepare a composition for an anti-fogging membrane, such that the viscosity was 47.1 mPa·s and the solid content was 22.5 mass%.
[0227] In addition, the amount of (meth)acrylic resin is not the amount as a resin solution (solid content: mass%), but represents the amount of resin (solid content) contained in the resin solution, and the amount of polyfunctional isocyanate compound is also represented as the amount as a solid content.
[0228] In addition, when 100 parts by mass of the above (meth)acrylic resin and 30 parts by mass of the polyol compound (polycaprolactone diol) were uniformly mixed, the measured hydroxyl value of the mixture was 93 mgKOH / g.
[0229] (Manufacturing of eyeglass lenses)
[0230] A thiourethane-based plastic lens MERIA (power S0.00) was used as a substrate, and the obtained anti-fog film composition was applied onto the substrate using a dipping method (pulling speed: 5 mm / sec) to form a film, and then heated at a temperature of 120°C for 120 minutes to manufacture an spectacle lens having a single layer of anti-fog film on the substrate. The results of the anti-fog film thickness, anti-fog performance evaluation, and appearance evaluation of the obtained spectacle lens are shown in Table 1.
[0231] [Examples 2–3, Comparative Examples 1–4]
[0232] In Example 1, an eyeglass lens was manufactured by the same operation except that ethyl acetate, methyl ethyl ketone, and diacetone alcohol were used to prepare the solid content and viscosity to the values listed in Table 1.
[0233]
[0234] From the results of the above examples and comparative examples, it can be seen that an eyeglass lens with excellent anti-fog properties and appearance is obtained by the method of the example.
[0235] Finally, the embodiments of the present disclosure are summarized.
[0236] The composition for an anti-fog film on eyeglass lenses, which is an embodiment of the present disclosure, has a viscosity of 20 mPa·s or more and 80 mPa·s or less at 15°C, and a solid content of 10 mass% or more and 25 mass% or less.
[0237] According to the embodiments described above, a composition for an anti-fog film on an eyeglass lens capable of manufacturing an eyeglass lens with excellent anti-fog properties and appearance, and an eyeglass lens with excellent anti-fog properties and appearance can be provided.
[0238] The embodiments disclosed herein should be considered as illustrative and not limiting in all respects. The scope of this disclosure is defined by the claims, not by the description above, and is intended to include all modifications within the meaning and scope equivalent to the claims.
[0239] In this disclosure, regarding the examples, contents, and various physical properties of each of the above components, matters described as examples or preferred ranges in the detailed description of the invention may be combined at will.
[0240] In addition, if the composition described in the example is adjusted to become the composition described in the detailed description of the invention, the disclosed embodiment can be carried out in the same way as the example across the entire claimed composition range.
Claims
Claim 1 A composition for an anti-fog film for eyeglass lenses comprising components (A) to (C), wherein the viscosity at 15 ℃ is 20 mPa·s or more and 80 mPa·s or less, and the solid content is 17 mass% or more and 25 mass% or less. Component (A): a (meth)acrylic resin having a constituent unit derived from a monomer (a-1) represented by the following general formula (1), a constituent unit derived from a monomer (a-2) represented by the following general formula (2), a constituent unit derived from a hydroxyalkyl (meth)acrylate (a-3), and a constituent unit derived from a monomer (a-4) represented by the following general formula (3). (A) Component (B): a polyol compound. (B) Component (C): a polyfunctional isocyanate compound. (C) [In general formula (1), R1 is a hydrogen atom or a methyl group, and R2 and R3 are each independently a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, and R2 and R3 may be the same or different.] [In general formula (2), R4 is a hydrogen atom or a methyl group, and m is an integer from 1 to 5.] [In general formula (3), R5 is a hydrogen atom or a methyl group, R6 is a divalent organic group, and n is an integer greater than or equal to 0 or 1.] Claim 2 A composition for an anti-fog film on eyeglass lenses according to claim 1, wherein the viscosity is 24 mPa·s or higher. Claim 3 An eyeglass lens having an anti-fog film formed by curing the composition for an anti-fog film for an eyeglass lens described in claim 1 or 2. Claim 4 In claim 3, the above anti-fog film is the outermost layer, an eyeglass lens. Claim 5 In claim 3, the eyeglass lens has a substrate and has a fogging film directly on the substrate. Claim 6 In claim 3, the above anti-fog film is a single layer, an eyeglass lens. Claim 7 delete Claim 8 delete
Citation Information
Patent Citations
Anti-fogging film forming material, Anti-fogging film forming coating liquid, Anti-fogging article, and production method thereof
JP2015030803A
Coating composition, cured film, and article having the cured film
JP2019094468A
